Systematic Review: Sweet Syndrome Associated with Inflammatory Bowel Disease. (23rd April 2021) - Sleiman, Joseph; Hitawala, Asif A; Cohen, Benjamin; Falloon, Katie; Simonson, Marian; Click, Benjamin; Khanna, Urmi; Fernandez, Anthony P; Rieder, Florian
Abstract: Background and Aims: Sweet syndrome [SS] is a dermatological condition associated with both inflammatory bowel disease [IBD] and azathioprine use. We performed a systematic review to better delineate clinical characteristics and outcomes of SS in IBD patients. Methods: Peer-reviewed, full-text journal publications from inception to April 2020 in English language and adult subjects with IBD were included. Skin biopsy was required as SS gold-standard diagnosis. Azathioprine-associated SS required recent azathioprine introduction or recurrence of SS after azathioprine re-challenge. Results: We included 89 publications with 95 patients [mean age of SS diagnosis: 44 years; 59% female; 20 with azathioprine-associated SS and 75 without]. SS was diagnosed prior to IBD in 5.3%, at time of IBD diagnosis in 29.5% and after diagnosis in 64.2%. In total, 91% of patients with SS had known colonic involvement and the majority [76%] had active IBD at diagnosis; 22% had additional extra-intestinal manifestations. Successful therapies for SS included corticosteroids [90.5%], anti-tumour necrosis factor [TNF]-α inhibitor therapy [14.8%] and azathioprine [11.6%]. Azathioprine-associated SS was distinct, with 85% male patients, mean age of SS diagnosis of 50 years and a lower likelihood to be prescribed corticosteroids for treatment [75% vs 94.7% of non-azathioprine-associated SS, p = 0.008]. All patients with azathioprine-associated SS improved with medication cessation and developed recurrence after re-challenge. Conclusions: SS may precede or occur with IBD diagnosis in almost one-third of cases. Azathioprine and IBD-associated SS present and behave distinctly, especially with regard to gender, age at diagnosis and recurrence risk. Corticosteroids and TNF-α inhibitors have demonstrated efficacy in treating SS in IBD.